DIGESTIBILITY AND ESTIMATION OF DIGESTIBLE ENERGY OF PALM KERNEL (ELAEIS GUINEENSIS) CAKE IN GUINEA PIGS (CAVIA PORCELLUS) - VELA-ROMÁN, LUIS (2024)
THE OBJECTIVE OF THE RESEARCH WAS TO DETERMINE THE DIGESTIBILITY OF THE NUTRITIONAL FRACTIONS OF PALM KERNEL CAKE AND TO ESTIMATE THE DIGESTIBLE ENERGY REQUIRED FOR THE FORMULATION OF RATIONS ACCORDING TO THE ANIMAL SPECIES. TEN MALE GUINEA PIGS (BODY WEIGHT: 725 ± 38 G) WERE DISTRIBUTED IN INDIVIDUAL METABOLIC CAGES. THE CONTROL GROUP (N: 5) WAS FED 100% WHEAT BRAN AND THE EXPERIMENTAL GROUP 40% PALM KERNEL CAKE AND 60% WHEAT BRAN. BOTH DIETS CONTAINED THE MINIMUM VITAMIN C REQUIREMENT. THE ADAPTATION PHASE TO THE NEW FEED LASTED 10 DAYS. FOR THE NEXT FIVE DAYS, 50 G OF FEED WAS FED AND FECES WERE COLLECTED DAILY. THE NUTRIENT DIGESTIBILITY COEFFICIENTS DETERMINED BY THE INDIRECT METHOD WERE 69; 70; 81; 61; 66 AND 53% FOR DRY MATTER, CRUDE PROTEIN, ETHER EXTRACT, CRUDE FIBER, NITROGEN FREE EXTRACT AND ASH, RESPECTIVELY. THE DIGESTIBILITY COEFFICIENTS, MULTIPLIED BY THEIR CALORIC VALUES, ALLOWED ESTIMATING THE DIGESTIBLE ENERGY, WHICH WAS 2720 KCAL/ KG OF PALM KERNEL CAKE. THE HIGH CARBOHYDRATE CONTENT OF PALM KERNEL CAKE CLASSIFIES IT AS AN ENERGETIC INGREDIENT. THE GOOD DIGESTIBILITY OF ITS NUTRITIONAL FRACTIONS AT THE DIGESTIVE LEVEL PROVIDES AMOUNTS OF DIGESTIBLE ENERGY SIMILAR TO THAT OF CONVENTIONAL INGREDIENTS USED IN THE INTEGRAL FEEDING OF GUINEA PIGS. © 2024, FUNDACION CIPAV. ALL RIGHTS RESERVED.